Best of both worlds: promise of combining brain stimulation and brain connectome - Luft, Caroline Di Bernardi; Pereda, Ernesto; Banissy, Michael J.; Bhattacharya, Joydeep (Frontiers in Systems Neuroscience, 2014)
Transcranial current brain stimulation (tCS) is becoming increasingly popular as a non-pharmacological non-invasive neuromodulatory method that alters cortical excitability by applying weak electrical currents to the scalp via a pair of electrodes. Most applications of this technique have focused on enhancing motor and learning skills, as well as a therapeutic agent in neurological and psychiatric disorders. In these applications, similarly to lesion studies, tCS was used to provide a causal link between a function or behaviour and a specific brain region (e.g., primary motor cortex). Nonetheless, complex cognitive functions are known to rely on functionally connected multitude of brain regions with dynamically changing patterns of information flow rather than on isolated areas, which are most commonly targeted in typical tCS experiments. In this review article, we argue in favour of combining tCS method with other neuroimaging techniques (e.g. fMRI, EEG) and by employing state-of-the-art connectivity data analysis techniques (e.g. graph theory) to obtain a deeper understanding of the underlying spatiotemporal dynamics of functional connectivity patterns and cognitive performance. Finally, we discuss the possibilities of these combined techniques to investigate the neural correlates of human creativity and to enhance creativity.